Analysis of co-creation experience and development of the ability of creativity and innovation in creating opportunities in the Indonesian handicraft industry - Nurgraha, Rd. Much.Jusup; Siddiq, Andhika Mochamad (Linguistics and Culture Review, 2022)
The purpose of this study is to look at analyzing the co-creation experience and development of creativity and innovation ability creating opportunities in the craft industry in Indonesia. This study is based on the phenomenon of the decline in the number of handicraft industries in Indonesia, factors that are thought to influence are lack of consumer involvement and increased creativity and innovation in the management of handicraft industries in Indonesia. Moreover, collected which were then analyzed using SPSS, SEM model (AMOS), and resulted in two independent variables influencing in creating new entrepreneurial opportunities, implying to create new business opportunities, must involve customer desires and increase the ability of creativity and innovation within the existing craft industry in West Java, Indonesia.